KAJIAN LITERATUR: ALERGI MAKANAN PADA ANAK DARI ASPEK IMUNOLOGII ASPEK IMUNOLOGI - Yustina Nuke Ardiyan; Diani Putri, Sukma (Jurnal Ilmu Keperawatan, 2022)
Food allergies in children are a common disorder in our circumstance. The basic theory of allergy is an excessive immune response or hypersensitivity reaction in the body. The role of T-helper (Th) cells is crucial in causing allergic reactions, including food allergies. The purpose of this paper is to discuss the phenomenon of food allergy in children in terms of immunological aspects. The research method used in this paper is by searching for articles from Google scholar related to food allergy. Results: Food allergies in children are mediated by Th, cytokines, and IgE. Several factors influence food allergy in children such as an impaired oral tolerance, microbiota imbalance, fast food, and cesarean delivery.